The impact of BMI and smoking on risk of revision following knee and hip replacement surgery: evidence from routinely collected data. Issue 9 (September 2019) - Burn, E.; Edwards, C.J.; Murray, D.W.; Silman, A.; Cooper, C.; Arden, N.K.; Prieto-Alhambra, D.; Pinedo-Villanueva, R.
Summary: Objective: The aim of this study was to assess the association of body mass index (BMI) and smoking with risk of revision following total knee replacement (TKR) and total hip replacement (THR). Design: Primary care data, from the Clinical Practice Research Datalink (CPRD), was linked to inpatient hospital records, from Hospital Episode Statistics Admitted Patient Care (HES APC), and covered 1997 to 2014. Parametric survival models, with BMI and smoking status included as explanatory variables, were estimated for 10-year risk of revision and mortality, and were extrapolated to estimate lifetime risk of revision. Findings: TKR and THR cohorts included 10, 260 and 10, 961 individuals, respectively. For a change in BMI from 25 to 35, the 10-year risk of revision is expected change from 4.6% (3.3–6.4%) to 3.7% (2.6–5.1%) for TKR and 3.7% (2.8–5.1%) to 4.0% (2.8–5.7%) for THR for an otherwise average patient profile. Meanwhile, changing from a non-smoker to a current smoker is expected to change the risk of revision from 4.1% (3.1–5.5%) to 2.8% (1.7–4.7%) for TKR and from 3.8% (2.8–5.3%) to 2.9% (1.9–4.7%) for THR for an otherwise average patient profile. Estimates of lifetime risk were also similar for different values of BMI or smoking status. Conclusions: Obesity and smoking do not appear to have a meaningful impact on the risk of revision following TKR and THR.